2019
DOI: 10.1002/cncr.32057
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent neoadjuvant chemotherapy and estrogen deprivation in patients with estrogen receptor–positive, human epidermal growth factor receptor 2–negative breast cancer (CBCSG‐036): A randomized, controlled, multicenter trial

Abstract: Background The current randomized, controlled, multicenter clinical trial was conducted to investigate the efficacy of concurrent neoadjuvant chemotherapy (NCT) and estrogen deprivation in patients with estrogen receptor (ER)–positive, human epidermal growth factor receptor 2 (HER2)–negative breast cancer. Methods Eligible patients with AJCC stage IIB to stage IIIC, ER‐positive, HER2‐negative breast cancer were enrolled and randomly assigned to receive NCT with or without estrogen deprivation. The primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“… 48 However, the advantage of concurrent neoadjuvant chemotherapy and hormone therapy in ER-positive breast cancer remains controversial. 49 , 50 , 51 In light of our study, we discovered that ERα renders chemoresistance by regulating p53-dependent gene transcription from lincRNA-p21 to DDB2 for DNA repair in mutp53-expressing breast cancer cells, supporting that the addition of the ER inhibitor to neoadjuvant chemotherapy provides the improvement of the clinical response in patients with ER-positive breast cancer, especially for those individuals with p53 mutations.…”
Section: Discussionmentioning
confidence: 63%
“… 48 However, the advantage of concurrent neoadjuvant chemotherapy and hormone therapy in ER-positive breast cancer remains controversial. 49 , 50 , 51 In light of our study, we discovered that ERα renders chemoresistance by regulating p53-dependent gene transcription from lincRNA-p21 to DDB2 for DNA repair in mutp53-expressing breast cancer cells, supporting that the addition of the ER inhibitor to neoadjuvant chemotherapy provides the improvement of the clinical response in patients with ER-positive breast cancer, especially for those individuals with p53 mutations.…”
Section: Discussionmentioning
confidence: 63%
“…Accordingly, concurrent neoadjuvant chemotherapy and estrogen deprivation had been proposed that whether NCT plus NET can convert to a higher tumor response. Several studies found that the combination neoadjuvant therapy appeared to improve the clinical response or shrinkage of tumor in ER+/HER2− BC (36)(37)(38), while inconsistent conclusion was reached that NCT plus NET as neoadjuvant therapy was not superior to NCT or NET alone in tumor response (39,40). More large-scale and high-quality prospective studies are required to follow these preliminary results to confirm the efficacy, safety and economic benefits of concurrent neoadjuvant chemotherapy and estrogen deprivation for HR+/HER2− BC patients, while in the future similar studies can involve CDK4/6 inhibitors into NET regimen to explore new fields.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only 2 patients (4.7%) achieved pCR. Recent publication by Yu et al [25] with the large cohort found the low pCR rate (7.2%) after neoadjuvant chemo-endocrine therapy in ER-positive and HER2-negaitve breast cancer. Ellis et al [26] suggested the triage to chemotherapy for patients with high Ki67 LI after neoadjuvant endocrine treatment is less effective in the American College of Surgeons Oncology Group Z1031 Trial.…”
Section: Discussionmentioning
confidence: 99%